2018
DOI: 10.1101/366237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Osmia bicornis is rarely an adequate regulatory surrogate species. Comparing its acute sensitivity towards multiple insecticides with regulatory Apis mellifera endpoints

Abstract: Bee species provide essential ecosystem services and maintain floral biodiversity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…As a first step in this exercise, we used the published acute contact toxicity data and, because the species tested varied widely in mass, we converted toxicity data for non‐ Apis bee species to common units [μg/ A. mellifera body weight equivalent (0.1 g)]. We used the mean of reported size ranges of non‐ Apis species to enable comparisons on a per weight basis to be conservative, i.e.…”
Section: Putting the Proposal To The Testmentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step in this exercise, we used the published acute contact toxicity data and, because the species tested varied widely in mass, we converted toxicity data for non‐ Apis bee species to common units [μg/ A. mellifera body weight equivalent (0.1 g)]. We used the mean of reported size ranges of non‐ Apis species to enable comparisons on a per weight basis to be conservative, i.e.…”
Section: Putting the Proposal To The Testmentioning
confidence: 99%
“…As a first step in this exercise, we used the published acute contact toxicity data 26,44 and, because the species tested varied widely in mass, we converted toxicity data for non-Apis bee species to common units [μg/A. mellifera body weight equivalent (0.1 g)].…”
Section: Putting the Proposal To The Testmentioning
confidence: 99%
“…However, recent research suggested that this may not always be a sound approach for several reasons. Firstly, Apis and non-Apis bees may vary in their susceptibility to pesticides and pesticides exposure opportunities may be different due to variations in feeding and breeding behavior, and chosen habitats [15][16][17][18][19]. There is also an issue on the metrics used for toxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously pesticide toxicity data for honeybees has until relatively recently been used as a protective surrogate for all bee species and even now, in many instances, this is still the case albeit a safety factor is applied which reduces the honeybee LD 50 value by a factor of 10. As there is continuing debate regarding the validity of using honeybees as a protective species [17,26], it is interesting to consider the statistical correlation between the two species based on the data collated for the dataset described herein. It should, however, be mentioned that this analysis is somewhat crude due to data limitations as the pesticide toxicity values for the two species have not been paired in terms of experimental conditions and worst case LD 50 values have been used to account for 'greater than' values.…”
Section: Insights Into the Datamentioning
confidence: 99%
“…LD 50 or NOAEL non-Apis bee = LD 50 or NOAEL honeybee / 10). This safety factor is based various comparative species sensitivity studies and covers the known variability among bee species (Areana & Sgolastra, 2014;Uhl et al, 2018;Heard et al, 2016;Roessink et al 2010).…”
Section: In-cropmentioning
confidence: 99%